Fetal position during pregnancy - Mehri F. (Iran University of Medical Sciences, 1988)
EXTRACT  In this study, position of fetus were examined in the different weeks of pregnancy and their association with fetus presentation in during labor. The study group included women who had normal condition. The aim of this study include:   1- To determine the distribution normal position of fetus before birth.   2- To determine the possibility of concurrent position of fetus in during pregnancy and maternity.   3- Show the relationship between the abnormal position of the fetus and being premature .   Study method: This study have been done on 11,593 pregnant women who have given birth in a hospital from October 1978 to December 1982 . Of these , 1678 patients who were referred to health centers and was normally performed ultrasound scan in 20, 30 and 36 week were selected.